Pero Jaji Wujud Karakter dan Entitas Keadaban Masyarakat Lio-Ende - Kami, Patrisius; Niron, Yakobus Lang Kelang; Ga’a, Adi Iswani Habibah (eScience Humanity Journal, 2025)
The role of culture in Indonesian society is extremely important as a manifestation of values and basic character in life, especially in the era of modernization which continues to develop without any boundaries. The cultural practices of communities in Eastern Indonesia and Lio-Ende in particular always show local characteristics in the form of traditions, expressions, customary sayings, and songs that contain meanings that represent thought patterns and even ways of life. Recent realities have become a challenge for the young generation of Lio-Ende who are already familiar with the rapid development of technology, such as information and communication technology, artificial intelligence, medical technology, and energy technology, which are characteristic of the modern era. On the other hand, this also has a significant impact on every aspect of their lives, potentially eroding local values and characteristics in the utilization of existing technology. This reality has led researchers to think it is essential to preserve and literate local values (customs and cultural values) to the younger generation through the Pero Jaji tradition. The objectives of this research are (1) To literate the younger generation about the importance of the Pero Jaji traditional agreement expression in Lio-Ende society as a manifestation of character and civilized entity. (2) To provide literacy books based on local wisdom (customs and cultural values). The method used in this research is a qualitative method conducted through direct observation, as it is based on an effort to understand and describe the intrinsic characteristics of phenomena that occur in Lio-Ende society. To achieve this, an ethnographic approach, in-depth interviews, document and cultural artifact analysis, surveys, and questionnaires are employed.